Speech acts - Searle, John R (University Press, 1970)
Includes bibliographical references.; Methods and scope -- Expressions, meaning and speech acts -- The structure of illocutionary acts -- Reference as a speech act -- Predication -- Three fallacies in contemporary philosophy -- Deriving "ought" from "is."